O PROBLEMĂ NOUĂ ŞI STRINGENTĂ PRIVIND FORMAREA CONTINUĂ A CADRELOR DIDACTICE PENTRU ÎNVĂŢÂMÂNTUL PRIMAR - USM ADMIN (Moldova State University, 2009)
In this article a new problem is presented: the continuous formation of the teachers working in the primary school. This problem is important for the development of ecological competence of teachers in their activity. As a result there are a lot of social, economic, political and scientific arguments, which demonstrate the correlation between this problem and the tendencies of educational development in the world.